Design optimization of a new W-beam guardrail for enhanced highway safety performance. (October 2017) - Yin, Hanfeng; Xiao, Youye; Wen, Guilin; Fang, Hongbing
Highlights: A new W-beam guardrail named as η-shaped W-beam guardrail (η-WG) was first proposed and investigated in this study. A dynamic RBF-based optimization design method was developed and used to optimize the η-WG. Compared with the traditional W-beam guardrail (TWG), the optimal design of η-WG can avoid tire snagging effectively and have excellent safety performance. Abstract: As one of the most widely used safety devices on highways, W-beam guardrail plays an important role in protecting errant vehicles from entering dangerous zones or colliding with oncoming vehicles. As one of the most widely used safety devices on highways, W-beam guardrails play an important role in protecting errant vehicles from entering dangerous zones or colliding with oncoming vehicles. One common issue with the traditional W-beam guardrails (TWG) is tire snagging which often occurred when the wheel of a striking vehicle entangled with a guardrail post. Tire snagging reduces the redirection performance of the guardrail and can result in serious injuries to the occupants. In this study, a new W-beam guardrail, named as "η-shaped W-beam guardrail (η-WG)", was developed using nonlinear finite element simulations combined with metamodeling-based design optimization methodology. The simulation results showed that tire snagging did not occur on the η-WG and the optimum design of the η-WG had an improved safety performance in vehicular crashes.